A comparative analysis of corpora allata-corpora cardiaca microRNA repertoires revealed significant changes during mosquito metamorphosis. (May 2018) - Nouzova, Marcela; Etebari, Kayvan; Noriega, Fernando G.; Asgari, Sassan
Abstract: The corpora allata (CA) are a pair of endocrine glands with neural connections to the brain and close association with another neuroendocrine organ, the corpora cardiaca (CC). The CA from adult female Aedes aegypti mosquitoes synthesize fluctuating levels of juvenile hormone (JH), which have been linked to the ovarian development and are influenced by nutritional signals. In this study, we investigated the potential involvement of microRNAs (miRNAs), a type of small non-coding RNAs, in the regulation of gene expression in CA-CC complexes during mosquito reproductive development, at stages with distinct JH biosynthesis patterns. We analyzed the miRNA repertoires expressed in the CA-CC of pupae, sugar-fed and blood-fed female Ae. aegypti . In total, 156 mature miRNAs were detected in the CA-CC, with 84 displaying significant differences in expression among the three CA-CC developmental stages. There were more miRNAs that were expressed in pupae, and decreased or were absent after adult emergence, when compared with changes between CA-CC of sugar and blood-fed females. Analysis of the genes identified as potential targets for the CA-CC miRNA repertoires classified them into the broad categories of metabolism, information storage and processing, and cellular processes and signaling; with genes involved in cellular processes and signaling representing the largest portion. Among them, the signal-transduction mechanisms and intracellular trafficking, secretion and vesicular transport contained almost 55% of the genes' targets. A substantial number of miRNAs were differentially abundant in the libraries of the three developmental stages, and those changes were much more notable when pupae and adult stages were compared. We detected putative binding sites for some of the most abundant miRNAs on genes encoding JH biosynthetic enzymes and CC neuropeptides. These studies should help us to gain a better understanding of the regulation of CA-CC activity mediated by miRNAs during major developmental stages in mosquitoes. Graphical abstract: Highlights: microRNA profiles of corpora allata and cardiaca in three developmental stages of Aedes aegypti mosquitoes were compared. Significant alterations of 84 microRNAs were found, in particular between the pupal and adult stages. A number of microRNAs were found to potentially target juvenile hormone biosynthetic enzymes. Gene ontology analysis of target genes of microRNAs revealed their involvement in various biological processes.